Infusion chemotherapy in malignant melanoma - Priario, Julio C (Cirugía del Uruguay, 1974)
A description is given of the perfusion method with Phenyl-Alanine-Mustard, in the treatment of malignant melanomas of the extremities. An analysis was made of the results obtained in 20 cases treated. Attention was called to the anatómopathological modifications which were observed, such as, reduction in the size of tt¡mor, necrosis of same, cell lysis, liberation of melanotic pigments, etc. 'I'he e:f'fect of the drug appears to be more significant in pigmented than in amelanotic tumors. In no case was total disappearance of the tumor achieved and, consequently, this method is considered as complementary to surgery.